Circulating miRNA expression in extracellular vesicles is associated with specific injuries after multiple trauma and surgical invasiveness - Groven, Rald Victor Maria; Greven, Johannes; Mert, Ümit; Horst, Klemens; Zhao, Qun; Blokhuis, Taco Johan; Huber-Lang, Markus; Hildebrand, Frank; van Griensven, Martijn (Frontiers in Immunology, 2023)
Two trauma treatment principles are Early Total Care (ETC), and Damage Control Orthopedics (DCO). Cellular mechanisms that underlie the connection between treatment type, its systemic effects, and tissue regeneration are not fully known. Therefore, this study aimed to: 1) profile microRNA (miRNA) expression in plasma derived Extracellular Vesicles (EVs) from a porcine multiple trauma model at different timepoints, comparing two surgical treatments; and 2) determine and validate the miRNA’s messengerRNA (mRNA) targets. The porcine multiple trauma model consisted of blunt chest trauma, liver laceration, bilateral femur fractures, and controlled haemorrhagic shock. Two treatment groups were defined, ETC (n=8), and DCO (n=8). Animals were monitored under Intensive Care Unit-standards, blood was sampled at 1.5, 2.5, 24, and 72 hours after trauma, and EVs were harvested from plasma. MiRNAs were analysed using quantitative Polymerase Chain Reaction arrays. MRNA targets were identified in silico and validated in vivo in lung and liver tissue. The arrays showed distinct treatment specific miRNA expression patterns throughout all timepoints, and miRNAs related to the multiple trauma and its individual injuries. EV-packed miRNA expression in the ETC group was more pro-inflammatory, indicating potentially decreased tissue regenerative capacities in the acute post-traumatic phase. In silico target prediction revealed several overlapping mRNA targets among the identified miRNAs, related to inflammation, (pulmonary) fibrosis, and Wnt-signalling. These were, among others, A Disintegrin and Metalloproteinase domain-containing protein 10, Collagen Type 1 Alpha 1 Chain, Catenin Beta Interacting Protein 1, and Signal Transducers and Activators of Transcription 3. Validation of these mRNA targets in the lung showed significant, treatment specific deregulations which matched the expression of their upstream miRNAs. No significant mRNA deregulations were observed in the liver. This study showed treatment specific, EV-packed miRNA expression patterns after trauma that correlated with mRNA expressions in the lungs, target organs over distance. A systemic response to the increased surgical trauma in the ETC group was identified, with various miRNAs associated with injuries from the trauma model, and involved in (systemic) inflammation, tissue regeneration. EV-transported miRNAs demonstrated a clear role in multiple trauma, warranting further research into tissue-tissue talk and therapeutic applications of EVs after trauma.